ECONOMIC DIVERSIFICATION AS A TOOL FOR POVERTY REDUCTION - Fozilov Vahobjon Akrom o’g’li (TADQIQOTLAR, 2026)
Annotation. This article examines the role of economic diversification in reducing poverty and ensuring sustainable economic development. The study analyzes how diversification of economic sectors contributes to employment growth, income stability, investment expansion, and social welfare improvement. Particular attention is paid to industrial diversification, service sector development, digital economy, innovation, and export diversification. The article also evaluates statistical relationships between diversified economic structures and poverty reduction indicators in developing countries.